Design and Manufacture of Automatic Collet Clamping Systems for Sprocket-CAM Handling on CNC Lathes - Ismartaya, Kristian; Wijaya, Thomas Ganda; Purnomo, Roberts; Karyadi, Gabriel Bagus (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
A proper clamping system reduces clamping time, enhances process repeatability, and increases flexibility in product replacement, significantly improving a company's competitiveness in terms of time and cost. The chamfering process for the KN-00XX series sprocket-cam product at PT. Toshin Prima Fine Blanking faced challenges due to the absence of a clamping device capable of quickly, securely, and automatically accommodating the contour clamping process while ensuring a long service life. To address this, optimizing existing spare parts, such as collets and pneumatic mechanisms, was essential to minimize manufacturing costs. This research aimed to design and evaluate a chuck tool that reduces product installation time and optimizes component stock to lower manufacturing costs. The study applied the VDI 2221-QFD method, where VDI 2221 identified functional requirements and user needs, while QFD assessed these needs and prioritized them for cost-effective design. Finite Element Analysis (FEA) was used to evaluate the design's strength and performance. The resulting pneumatic collet clamping design showed an actual von Mises stress value of 1,044,029 kN/m², safely below the maximum allowable value of 1,080,000 kN/m². FEA analysis indicated a collet displacement of 0.37 mm, close to the actual measured value of 0.42 mm, meeting clamping requirements. The estimated manufacturing cost of the pneumatic collet clamping system was Rp. 1,472,769. Actual trials demonstrated an average cycle time of 9.8 seconds, confirming that the pneumatic collet clamping design is safe, efficient, and fulfills specified requirements.